Literature of travel and exploration : an encyclopedia - Speake, Jennifer (New York : Fitzroy Dearborn, 2003)
"Connoisseurs of travel writing and those planning a trip will delight in this new encyclopedia. Entries describe journeys, voyages, and routes; world travelers and their writings in diaries, letters, logbooks, and postcards; remarkable destinations; geographers and cartographers; and contemporary travel writers and their works. Author entries include biographical profiles. Each entry is complete with a list of references and further readings. Volume one contains two listings that are useful for browsing the three-volume set -- an alphabetical listing of entries and a thematic list of entries. Volume three has a bibliography of all works and articles referenced in the entries as well as a general index."--"The Top 20 Reference Titles of the Year," American Libraries, May 2004.
v. 1. A - F -- v. 2. G - P -- v. 3. R - Z, Index.
Keywords: Voyages and travels; Travelers' writings; Travel writing